Influência da exposição subletal ao clorantraniliprole sobre o desenvolvimento larval, morfometria e a formação da musculatura de voo de Scaptotrigona postica (Latreille, 1807) - Carraro, Laís (Universidade Federal de São Carlos, 2025)
Bees are the main pollinators of both natural and agricultural environments, visiting approximately 90% of crop species, of which 48% are directly related to human food production. During foraging, they may collect pollen and nectar contaminated with pesticides, such as chlorantraniliprole, and transport them back to the hive. As a result, larvae are exposed to these residues, which can compromise their development and affect the formation of essential tissues, such as flight musculature. This study evaluated the effects of sublethal concentrations of chlorantraniliprole on larval development, morphometry, and flight muscle formation in Scaptotrigona postica bees. For this, larvae were exposed to five treatments: negative control (CN – food only); positive control (CP – dimethoate at 6.9 ng a.i./larva); solvent control (CA – acetone at 0.2%); chlorantraniliprole 1 (CL1 – 2.04 ng a.i./larva); and chlorantraniliprole 2 (CL2 – 0.204 ng a.i./larva). During development, key milestones were recorded: entry into the fifth instar (5°I), defecation (DF), pupae with different eye colors (PB – white; PR – pink; PM – brown; PP – black), and emergence (EM), in addition to daily monitoring of mortality. Mortality, pupation, and emergence rates were determined. Emerged bees were subjected to morphometric analyses of head width (MC) and intertegular distance (MI). Simultaneously, the flight muscles were dissected and histologically analyzed using Hematoxylin and Eosin (HE), Periodic Acid-Schiff (PAS), Methylene Blue (AM), Mallory’s Trichrome (MY), and Masson’s Trichrome (MN). Additionally, nuclear measurements of muscle cells were performed. Data normality was assessed, and ANOVA/Tukey or Kruskal-Wallis/Dunn tests were applied accordingly. The Kaplan-Meier method was used to construct the survival probability curve. Results indicated that only CP caused toxicity, presented by impacts in rates of larval mortality, pupation, and emergence, as well as in mortality during each developmental stage. Regarding developmental progression, only CL2 showed significant differences in mortality from DF to PB and from PR to PM. Although no lethal effects were observed within the same stage, mortality rate variation was noted during the 5°I period between CA and CL2. The Kaplan-Meier curve and Mantel-Cox Log-Rank test revealed a significant decrease in survival probability for larvae exposed to CL2. Morphometric analyses showed a significant increase in head width in CL1 and in intertegular distance in CL2. Histological analyses of the flight muscles revealed that both CL1 and CL2 presented focal points of tissue disorganization, presence of cytoplasmic vacuoles, and alterations in muscle fibers. Additionally, hemocytes were observed within the extracellular matrix and among muscle fibers. It is concluded that, although chlorantraniliprole did not induce larval mortality or inhibit pupation and emergence rates, it negatively influenced development and morphometric parameters. Furthermore, it caused significant damage to the formation of the flight musculature, which is essential for foraging activity.
Sublethal exposure to chlorantraniliprole affects larval development, morphometry, and flight muscle formation in Scaptotrigona postica (Latreille, 1807)
Keywords: Agrotóxicos; Diamidas; Meliponini; Mandaguari; Abelha sem ferrão; Pesticides; Diamides; Stingless bee; CIENCIAS AGRARIAS